VOICES OF CONFIDENCE: AN EMPIRICAL AND LITERATURE REVIEW OF STUDENTS’ EXPERIENCES WITH SELF-EFFICACY IN WRITING - arifin, arifin (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This article discusses some writing difficulties faced by university students, and experts strategies to improve self-efficacy and the different aspects of self-efficacy in building students' confidence in writing. The purpose of this article is to provide a comprehensive overview of the word "self-efficacy," as well as the effects of writing anxiety and motivation on EFL university students' self-evaluative judgments of corrective feedback. Researcher used an empirical study by delivering questionnaires to 238 university students and strengthening students’ experience by stating the relevant experts’ perspectives on their paper's findings. The study's findings have implications; first, the results of this study provide implications for lecturers' Pedagogical Practices in improving students' self-confidence competence in writing. Second, lecturers' teaching implementation should encourage and support students' writing development, especially on writing strategies, and individualised support based on students' level of self-efficacy. The last is that an intervention programme is needed for low writing self-efficacy and focuses on building students' confidence, and fostering a growth mindset towards writing. his research highlights the significant role of self-efficacy in student writing success. The findings suggest three key areas for improvement: pedagogical practices that boost writing confidence, teaching strategies that provide individualized support and promote writing development.